The Influence of Price, Product Quality and Service Quality on Consumer Satisfaction at TNA Collection Store of Prambon, Nganjuk - M. Anas; Laelatul Zahro; Bayu Surindra (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The purpose of this study was to determine the impact of price, product quality and service quality on customer satisfaction at the TNA Collection Prambon Nganjuk store. The samples in this study were consumers/buyers who bought products/goods, whether they made an order/purchase by coming directly to the store. The method used to take the sample was to simple random sampling method and the numbers of samples were calculated by the Slovin formula which obtained total sample of one hundred respondents. The use of quantitative methods used in this study was applied with a causality design technique. The analysis in this study used multiple linear regression analysis. The result of this research was an: 1) The price partially did not have an impact on customer satisfaction. 2) The quality of the product partially affects consumer satisfaction. 3) The quality of service partially had an influence on customer satisfaction. 4) price (X_1), product (X_2) quality and service quality (X_3) simultaneously affected consumer satisfaction as indicated by the results of the f test and the significant probability value was 0.000 <0.05 and the F counted (25,086)>F table (2,698) with the influence of price (X_1), product quality (X_2) and the quality of service (X_3) on customer satisfaction TNA Collection store by 43.9% and the rest was not studied in this study.